(untitled) (Scottish Historical and Archaeological Internet Reports, 2011)
The discussion covers the development and expansion of the medieval burgh in the 11th-14 centuries, the town ditch in the mid 14th century, life in the Cowgate in the early 15th century, 15th-century midden dumps, the recut of the town ditch in the late 15th century and developments during the 16th and 17th centuries.